Evaluation of Postoperative Complications Between Total and Subtotal Thyroidectomy For Multinodular Goiter - Masood, Sajea; Kanaan, Samir; Khaddouj, Mohammad (Latakia University Journal -Medical Sciences Series, 2019)
Backgound: To assess the incidence of early postoperative complications among a group of patients who underwent total eradication and another group that underwent subtotal bilateral removal. Patients and Methods: A retrospective study was conducted for all patients of the multinodular thyroid product admitted to the General Surgery Division of the Faculty of Medicine Hospitals in Lattakia between (1-1-2015) and (1-1-2018) who underwent surgical treatment in two ways. (total thyroidectomy – subtotal thyroidectomy). Results: The study included (200) patients (166) patients (83%) of the cases were subjected to (TT) and (34) patients (17%) of the cases underwent (BST). The age of patients of the research sample ranged between 25 and 65 years, the average age of 46.6 ± 6.7 years. The number of women in the study groups (173) patients (86.5%) and the number of men in the study groups (27) patients (13.5%). Temporary paralysis of the recurrent laryngeal nerve occurred in 9 patients (5.4%) in the TT group, while only two patients (5.9%) in the BST group, (P = 0.83). Important. There was permanent paralysis of the recurrent laryngeal nerve in two patients (1.25%) in the TT group, whereas no permanent paralysis in the recurrent laryngeal nerve was observed in any patient in the BST group, (P = 0.5). Important. There was a temporary hypothyroidism in (23) patients (13.9%) in the TT group, while (3) patients (8.8%) in the BST group, (P = 0.014). Two study groups in terms of the incidence of temporary hypothyroidism. One patient (0.62%) in the TT group had permanent hypothyroidism, whereas no patient in the BST group had permanent hypothyroidism (P = 0.33). Conclusions: Total thyroidectomy (TT) is a safe procedure for patients with a benigen multinodular thyroid in terms of incidence of recurrent laryngeal nerve and thyroid injury except for a higher risk of temporary hypothyroidism أهمية البحث: تقييم حدوث المضاعفات الباكرة بعد الجراحة بين مجموعة من المرضى خضعت للاستئصال التام و مجوعة أخرى خضعت للاستئصال تحت التام ثنائي الجانب. المرضى و طرائق البحث: تم إجراء دراسة استرجاعية لجميع مرضى السلعة الدرقية متعددة العقد المقبولين في شعبة الجراحة العامة في مشافي كلية الطب باللاذقية في الفترة الواقعة بين (1-1-2015) و (1-1-2018) و اللذين خضعوا للمعالجة الجراحية بطريقتين (الاستئصال التام – تحت التام). النتائج: شملت الدراسة (200) مريض منهم (166) مريض أي (83%) من الحالات خضعوا ل(TT) و (34) مريض أي (17%) من الحالات خضعوا ل(BST). تراوحت أعمار مرضى عينة البحث بين 25 و 65 سنة, بلغ متوسط أعمارهم 46.6±6.7 سنة. عدد النساء في مجموعتي الدراسة (173) مريضة أي (86.5%) و عدد الرجال في مجموعتي الدراسة (27) مريض أي (13.5%). حدث شلل مؤقت في العصب الحنجري الراجع لدى (9) مرضى أي (5.4%) في مجموعة ال(TT), بينما حدث لدى مريضين فقط أي (5.9%) في مجموعة ال(BST), ( P= 0.83 ) لا يوجد فرق إحصائي هام. حدث شلل دائم في العصب الحنجري الراجع لدى مريضين أي (1.25%) في مجموعة ال(TT), بينما لم يسجل حدوث شلل دائم في العصب الحنجري الراجع لدى أي مريض في مجموعة ال(BST), (P=0.5) لا يوجد فرق إحصائي هام. حدث قصور جارات الدرق المؤقت لدى (23) مريض أي (13.9%) في مجموعة ال(TT), بينما حدث لدى (3) مرضى أي (8.8%) في مجموعة ال(BST), ( P=0.014 ) يوجد فرق إحصائي بين مجموعتي الدراسة من حيث حدوث قصور جارات الدرق المؤقت. حدث قصور جارات الدرق الدائم لدى مريض واحد أي (0.62%) في مجموعة ال(TT), بينما لم يحدث قصور جارات الدرق الدائم لدى أي مريض في مجموعة ال(BST), ( P= 0.33 ) لا يوجد فرق إحصائي هام. الاستنتاجات: يعتبر الاستئصال التام للغدة الدرقية (TT) إجراءاً آمناً لمرضى السلعة الدرقية السليمة متعددة العقد من حيث حدوث أذية العصب الحنجري الراجع و أذية الدريقات باستثناء وجود خطورة أعلى من حيث حدوث قصور الدريقات المؤقت.